2009
DOI: 10.1111/j.1574-6941.2009.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

Rumen protozoa are rich in polyunsaturated fatty acids due to the ingestion of chloroplasts

Abstract: Within this study, we investigated whether the polyunsaturated fatty acids (PUFA)-rich nature of rumen protozoa is a consequence of ingestion of PUFA-rich chloroplasts. Four Hereford x Friesian steers were offered hay [low 18:3 (n-3) and low chlorophyll concentration] followed by freshly cut perennial ryegrass [high 18:3 (n-3) and high chlorophyll concentration] for 16 days. On the 14th and 16th days, rumen protozoa as well as attached and planktonic bacteria were fractionated 1 h before (-1 h), 2 and 6 h post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
44
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 49 publications
7
44
0
1
Order By: Relevance
“…However, in vivo microbial communities composition associated with changes in biohydrogenation have had low correlation 19, 20 and limited explanation of it association 21 . Therefore, further integration of omics technology might be a useful strategy to understand how the shift in the ruminal bacteria population affect the ruminal metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…However, in vivo microbial communities composition associated with changes in biohydrogenation have had low correlation 19, 20 and limited explanation of it association 21 . Therefore, further integration of omics technology might be a useful strategy to understand how the shift in the ruminal bacteria population affect the ruminal metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh forage is typically composed of approx. 50 % 18:3 n-3, 15 % 18:2 n-6 and 15 % 16:0 with the rest being minor contributions from other fatty acids (Huws et al 2009; Huws et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…A recent study by Huws et al (2009a) showed that the engulfment of chloroplasts is a major contributor to the high LNA concentration of protozoa. This cannot explain the high concentration of CLA and VA in protozoa, however, as these FA are absent from the plant material.…”
Section: Biohydrogenating Activity In the Rumenmentioning
confidence: 99%